(untitled) (Al-Aasar, 2025)
History is one of the oldest human sciences. Governments, states, and dynasties have been interested in recording the events of their time. In the Indian subcontinent, historical works have also been compiled since ancient times. One type of these histories is local history, that is, works that narrate the history of a part of this ancient and vast land. Among the anonymous works written in the local history of the Deccan is the Amir Nameh, which deals with the life and military exploits of Amir al-Dawlah. The main importance of this work is that it is in Persian language. The author of this work is Basawan Lal (d. 1247AH), who began writing this work in 1230AH, at the behest of Amir Khan and the encouragement of his son, Wazir al-Dawlah Muhammad, and continued writing until his death. Several manuscripts of this work exist. There have also been translations of it. This number of copies and translations indicates the importance of this work. However, the Amir Nameh has not been edited yet. The authors of the present article have introduced Amir Khan and Basavan Lal and have compiled some of its literary and historical features.